Kepemimpinan Kepala Madrasah dalam Membangun Budaya Madrasah Yang Kondusif di Madrasah Aliyah Negeri - Astuti Astuti; Danial Danial (El-Idare, 2019)
This research aims to describe the leadership role of the headmaster in building aconducive madrasah culture in the MAN Bone District. This research is a field study with a qualitative approach. The data collection techniques used are interviews and observations. The subject of this study is the headmaster, deputy chief of madrasah, teachers, administration staff, and students. Data is analyzed by reducing data, presenting data, and drawing conclusions. The results of this study show that the headmaster performs its role in developing cultures in terms of values, such as initiative, togetherness, responsibility, sense of existence, commitment, cooperation, mutual understanding, spirit of unity, obedience azas, guiding and motivating, innovative, hard-working, caring, discipline and honesty, clean culture, good relationships, knowledgeable, and so on. The obstacles in the development of madrasah culture are more dominant in difficulty in applying discipline perfectly. Discipline will be difficult to manifest without awareness of each individual. Therefore, the headmaster always seeks to have discipline always enforced and forward through the consciousness of the residents of the madrasah for his responsibilities in carrying out duties in the madrasah.